Automation and Human Synergy: Redefining Work in the Digital Enterprise - Katiyar, Jimmy (European Journal of Computer Science and Information Technology, 2025)
The fast paces of automation in enterprise settings are essentially transforming work relationships and the human role. With routine activities being taken over by intelligent technologies, professionals are being drawn more towards strategic, creativity and people-dimensions that play to uniquely human strengths. Such a shift asks organizations to embrace humanity by focusing on approaches that consider both the technological growth and the growth of the workforce, where automation is used as a supplement to the human input, not as a substitute. The transformation requires careful deliberation of governance systems, skills enhancement procedures, ethics and broader measures of success than efficiency in operation. If the challenges such as the perils of over-automation, tensions in customer experience, concerns about displacement of workforce, and digital divides are tackled, then the organizations will be capable of establishing long-term models of automation that allocate the rewards and benefits fairly and avoid eliminating the meaningful work of humans. The workplace of the future can be characterized as a collaborative space in which the potential of humans and the power of technology are joined to produce greater results than either could produce alone.